He-Wei granules (HWKL) combat cisplatin-induced nephrotoxicity and myelosuppression in rats by inhibiting oxidative stress, inflammatory cytokines and apoptosis. Issue 32 (4th April 2017) - Song, Zehai; Chang, Hang; Han, Na; Liu, Zhihui; Liu, Ye; Wang, Hui; Shao, Jingxuan; Wang, Zhonglin; Gao, Hao; Yin, Jun
Abstract : He-Wei granules (HWKL) combat cisplatin-induced nephrotoxicity and myelosuppression in rats by inhibiting oxidative stress, inflammatory cytokines and apoptosis Abstract : As a highly effective antineoplastic chemotherapeutic drug, cisplatin is widely used clinically to treat a variety of human malignancies. However, its clinical use is severely limited by serious side-effects, of which nephrotoxicity and myelosuppression are considered to be the most important because they significantly reduce patient life quality and hinder effective use. In this study, we investigated whether HWKL, a product obtained from modified Ban-xia xie-xin decoction first described 1700 years ago, exhibits protective effects against cisplatin-induced nephrotoxicity and myelosuppression. After intraperitoneal injection of 7 mg kg −1 cisplatin to Wistar rats, nephrotoxicity and myelosuppression were observed. HWKL reduced cisplatin-induced elevations in blood urea nitrogen (BUN) and serum creatinine (Scr) levels, increased water intake and improved renal tubular lesions. Cisplatin-induced increases in tumor necrosis alpha (TNF-α) protein, interleukin-1 beta (IL-1β) protein, cyclooxygenase-2 (COX-2) protein, extracellular signal-regulated kinase (ERK), TNF-α mRNA and IL-1β mRNA were significantly reduced by HWKL and cisplatin-induced oxidative stress was also inhibited by HWKL. Furthermore, HWKL contributed to increase immunological function to combat cisplatin-induced myelosuppression. Our findings indicate that HWKL inhibits cisplatin-induced nephrotoxicity and myelosuppression via several mechanisms which operate simultaneously and provide basic evidence to confirm that HWKL could be useful in clinical situations as a protective agent to prevent cisplatin-induced nephrotoxicity and myelosuppression.